Integrating peace and unification concepts in a Korean language class in the graduate school - Ancho, Inero (Universitas Pendidikan Indonesia (UPI), 2022)
Complex and diverse as it may seem, peace education in a nutshell can be viewed as an approach that embeds theory, practice, and research of numerous fields of study that serve as off-shot for interests on respect for tolerance, understanding diversity, and respect for human rights.With this research, it could be noted that the context could also be employed as a vehicle in advancing socio-cultural trends and issues regarding the country under study. It provides opportunities for meaningful interaction and discourse beyond language, grammar, and vocabulary. The main purpose of the study is to describe the experiences and perspectives of Filipino graduate students regarding learning Korean as a foreign language with emphasis on peace and unification concepts. The present study was conducted using qualitative research case study through content analysis. This case study involved Filipino graduate students in a Korean language class as the participants. The results showed that foreign, diplomatic, and political issues have reached the classrooms. The students did not just consume theories, but the practice of these concepts was highly sought. Topics focusing on peace and unification were seen to be critical and crucial for the contemporary era as well for the future of humanity. The present study concludes how peace and unification can be aimed at nurturing students that mindset that cultivate values and attitudes towards tolerance, understanding, and sensitivity.